The use of Langmuir-Blodgett films of a perylene derivative and polypyrrole in the detection of trace levels of Cu2+ ions - Antunes, P. A.; Santana, C. M.; Aroca, R. F.; Oliveira, O. N.; Constantino, CJL; Riul, A. (Elsevier B.V., 2005)
Langmuir films of a tetracarboxylic perylene derivative and polypyrrole display condensed surface pressure isotherms that are shifted when Cu2+ ions are added to the ultrapure water subphase. These films were transferred onto interdigitated gold electrodes leading to Y-type Langmuir-Blodgett (LB) films. The electrodes modified with 5-layer LB films were immersed into a flask with ultrapure water and water containing Cu2+ ions at concentrations ranging from mM to muM. Impedance measurements indicated a distinct electrical response for the two types of films. Although the materials chosen have no specificity for ionic metals, they can be combined for detecting trace levels of Cu2+, which may be exploited in water quality monitoring. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Langmuir-Blodgett films; BuPTCD; Ppy